THE IMPACT OF ECONOMIC GROWTH, EDUCATION AND OPEN UNEMPLOYMENT ON POVERTY IN INDONESIA - Dina Yuliana; Saharuddin Saharuddin; Jariah Abu Bakar; Umaruddin Usman (LPPM Universitas Malikussaleh, 2025)
This study aims to determine the effect of economic growth, education,and open unemployment on poverty in Indonesia from 1990 to 2024. Thedata used in this study is secondary data in the form of annual time seriesfrom 1990 to 2024 obtained from the Indonesian Central StatisticsAgency. The analysis method used is Autoregressive Distributed Lag(ARDL) regression analysis with a quantitative approach using theEviews 12 program. The results show that the economic growth variablein the short and long term has a negative and significant effect on povertyin Indonesia. The education variable (RLS) in the short term does nothave a significant effect on poverty in Indonesia, but in the long term,economic growth has a negative and significant effect on poverty. Theopen unemployment variable in the short term has a negative andsignificant effect on poverty, but in the long term, open unemployment hasa positive and significant effect on poverty in Indonesia.